Theoretical reflections about the production of knowledge and the entrepreneurial university (Dissertare, 2020)
The present essay, of a descriptive and reflective nature, is intended to refer to the essential elements of six models of knowledge creation, with a view to their connection with the promotion of entrepreneurial initiatives in and through universities. For this, the subject of entrepreneurial university is approached in a complementary manner, proposing alternatives that, together with structural adjustments, could contribute not only as additional sources of income for the sector, but also as ways to generate changes in the academic sphere that strengthen the connections between university functions, and in a practical way, the impact of advances, outcomes and solutions that can be transferred and managed in different areas of society is strengthened from the university.
Keywords: university research; knowledge models; entrepreneurial university